Congenital dyserythropoietic anemia masquerading as hereditary spherocytosis - Kaninika Sanyal; K. Jai Kumar; Mrinalini Kotru; Mukul Aggarwal; Pooja Dewan (Elsevier, 2024)
Background: Congenital dyserythropoietic anemias (CDA) type II is a rare hereditary chronic hemolytic anemia due to a defect in the SEC23B gene which shows varying degrees of ineffective erythropoiesis and is often misdiagnosed as a red blood cell (RBC) membranopathy or enzymopathy. Case report: A five-year-old boy was admitted with increasing paleness for one month. Examination revealed pallor, icterus, and hepatosplenomegaly. Based on the peripheral blood smear findings, increased osmotic fragility of RBCs and a suggestive eosin-5'-maleimide binding test, the initial diagnosis was hereditary spherocytosis. However, the bone marrow aspirate suggested CDA. Next-generation sequencing revealed a SEC23B-Y462C homozygous mutation in exon 12 confirming CDA type II. Conclusion: CDAs are often underdiagnosed since the morphological abnormalities and clinical features resemble other hemolytic anemias. In this case, we demonstrate approach to diagnosis, highlighting the interpretation of the laboratory investigations and a timely bone marrow examination.